2021
DOI: 10.1142/s0192415x21500622
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Artificial Intelligence on Traditional Chinese Medicine

Abstract: Traditional Chinese Medicine (TCM) is a well-established medical system with a long history. Currently, artificial intelligence (AI) is rapidly expanding in many fields including TCM. AI will significantly improve the reliability and accuracy of diagnostics, thus increasing the use of effective therapeutic methods for patients. This systematic review provides an updated overview on the major breakthroughs in the field of AI-assisted TCM four diagnostic methods, syndrome differentiation, and treatment. AI-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 71 publications
0
31
0
1
Order By: Relevance
“…Above all, we define what the "knowledge" in the KG is. For the SYN2 shown in Figure 2, one of the knowledge about SYN2 denoted as Knowl SYN2 can acquire by (2) and the result as (3).…”
Section: Definitions and Task Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Above all, we define what the "knowledge" in the KG is. For the SYN2 shown in Figure 2, one of the knowledge about SYN2 denoted as Knowl SYN2 can acquire by (2) and the result as (3).…”
Section: Definitions and Task Complexitymentioning
confidence: 99%
“…During clinical diagnosis, doctors integrate TCM theories to identify the syndrome based on patients' symptoms, which are heavily influenced by the doctor's previous experience. AI-assisted TCM diagnosis relies primarily on digital data obtained by modern electronic instruments, making TCM diagnosis more quantitative, objective, and standardized [ 3 ]. Thus, it is necessary to have a computer-aided decision-making model for the diagnosis to balance the uncertainty of human factors.…”
Section: Introductionmentioning
confidence: 99%
“… 15 16 In recent years, several studies have summarized the characteristics of symptoms in TCM and found that diagnosis in TCM can be achieved by bionics instruments. 17 19 The application of ICT in the field of medicine and health has become normal, and several TCM doctors have begun using devices as diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
“…TCM has played a crucial role in the treatment of many diseases of Chinese people, such as diabetes, cancer and RA, etc. ( Li et al, 2021a ; Wang et al, 2021b ; Wang et al, 2021d ; Xiang et al, 2021 ). Especially since the outbreak of COVID-19, TCM has played its unique advantages and gradually gained recognition abroad ( Hou et al, 2021 ; Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of science and technology, AI has attracted much attention in the field of TCM. The application of AI has not only observably improved the reliability and accuracy of diagnosis, but also provides favorable conditions for screening suitable TCM or program for disease treatment, as well as promoting the modernization of traditional medicine ( Wang et al, 2021d ). At present, the establishment of new methods such as systems biology, bioinformatics, integrated pharmacology and network pharmacology has brought new hope for the modernization of TCM research ( Ren et al, 2020 ; Shen et al, 2020 ; Wang et al, 2021c ; Fang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%